Collaborative Governance in Indonesian Waste Management: A Systematic Literature Review - Fadhlan, Muhammad (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This systematic literature review examines the implementation and dynamics of collaborative governance in waste management across Indonesia. Study uses a literature review method to identify, analyze, and synthesize scientific findings related to the application of collaborative governance in waste management in Indonesia. Focusing on collaborative governance models, regional case studies, barriers, and enabling factors in Indonesia waste management. The findings reveal that while collborative governance engaging government, private sector, and community stakeholders has been widely adopted in policy and practice, its effectiveness is often constrained by asymmetrical power relations, fragmented institutional arrangements, limited community participation, and insufficient private sector involvement. Case studies from cities such as Malang, Bali, Bandung, Gresik, and others highlight both successful initiatives like waste banks and public-private partnership, and persistent challenges including weak law enforcement, lack of shared goals, and resource limitation. The review underscores the need for a shift from symbolic participation to genuine co-creation, recommending institutional reforms such as multi-stakeholder forums, formal recognition of informal actors, facilitative leadership, and digital infrastructure for monitoring and feedback. Ultimately, strengthening collaborative governance is essential for achieving sustainable waste management and advancing Indonesia’s environmental and development goals.